Mapping Gendered Communications, Film, and Media Studies: Seven Author Clusters and Two Discursive Communities - Kim Britt Pijselman; Miklós Sükösd (Publications, 2023)
This study examined and mapped the extent to which gender became incorporated into the intersecting research fields of communications, film, and media studies. A total of 8054 academic publications from these disciplines, indexed in the Web of Science between 1975 and 2022 (ndocs = 8054), were extracted to create two types of bibliometric maps: (a) an author co-citation map, and (b) a co-occurrence map of key terms (taken from keyword lists, titles, and abstracts of publications). Our results revealed a pattern of seven distinct clusters of 995 authors (nauthors = 995) in the field. Additional research is needed to analyze the internal structure of these seven clusters, and label them accordingly. The key terms in the same authors’ works, however, show a distinctively different pattern, namely a divided, dichotomous, polarized structure (nterms = 720). Judging from this, we hypothesize that gender is discussed in two main ways: either as a critical concept concerning discourses, representations, and other social and cultural constructs, or as a variable in more formal sociological and psychological research designs. The conceptual framework and results of the present study lay the foundation for further research regarding the diverse academic agendas of the seven author clusters, the split nature of their discursive communities, as well as the key difference between the two patterns.